2021
DOI: 10.1002/adfm.202105645
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Sensors in Biotechnology

Abstract: As populations expand worldwide, medical care will need to diversify its data collection techniques to be able to provide adequate healthcare to global populations, this can be achieved through point-of-care analysis by wearable analytical devices. Holographic sensors are reusable optical biosensors with the capability to continuously monitor variations, generating the prospect of in vivo monitoring of patient homeostasis. Holographic optical sensors have emerged as an opportunity for low cost and real-time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 123 publications
0
19
0
Order By: Relevance
“…Several previous articles refer to fabrication by holographic lithography that focus on the theoretical point of view and are based on photoresist materials [44] or, more interestingly, comprise all the materials employed in holographic sensors [42,43]. Here we briefly review the fabrication processes employed to date to create diffraction patterns on hydrogels.…”
Section: Holographic Lithography Fabrication Modes In Hydrogels For S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous articles refer to fabrication by holographic lithography that focus on the theoretical point of view and are based on photoresist materials [44] or, more interestingly, comprise all the materials employed in holographic sensors [42,43]. Here we briefly review the fabrication processes employed to date to create diffraction patterns on hydrogels.…”
Section: Holographic Lithography Fabrication Modes In Hydrogels For S...mentioning
confidence: 99%
“…Although previous reviews of holographic sensors have been published [42,43], they center on volume and phase holograms, or include different materials, like polymers or gelatin, which makes it difficult to distinguish the exact achievements and applications of hydrogel-based holographic systems. Here, we review the examples found in the literature that involve holographic lithography and responsive hydrogels, and focus on biosensors by analyzing their fabrication, measurement principles, and detection setups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] Holographic sensors are ideally placed to facilitate the progression towards POC devices, due to their real‐time, label‐free readout, low cost, and reversibility. [ 5 ] Recent holographic technologies show a primary focus to biomedical applications, [ 6 ] such as sensing pH, [ 7 ] heavy metals, [ 8 ] glucose, [ 9 ] ions, [ 10 ] and lactate. [ 11 ] Holographic recordings can be constructed with additional information such as text to convey further information to users offering both qualitative visual analysis and quantitative measurements through the combination with smartphone applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the well-established use of holographic gratings as sensors has led to many forms being developed in this research field. Surface relief gratings, inverse opals, metal nanoparticle and nanoparticle-free holographic sensors are used in medical and biological applications [ 1 ] or as humidity and temperature sensors [ 2 ], whereas flexible substrates are used for the detection of bending deformations [ 3 ] and pressure sensors [ 4 ]. Regarding pressure sensors, reflection phase holograms recorded in polymer mixtures are used to detect pressure changes by monitoring the reflection peak position as a function of the applied pressure.…”
Section: Introductionmentioning
confidence: 99%